Herbage Characteristics of Continuously Stocked Limpograss Cultivars under Stockpiling Management - Vendramini, Joao M. B.; Sollenberger, Lynn E.; Leite de Oliveira, Fabio C.; Herling, Valdo R.; Gomes, Vinicius C. [UNESP]; Sanchez, Joao M. D.; Yarborough, James K. (Crop Science Soc Amer, 2019)
Limpograss [Hemarthria altissima (Poir.) Stapf & C.E. Hubb.] is commonly used as stockpiled forage. Variation in forage characteristics during the stockpiling period may affect supplementation strategies. Our objective was to characterize herbage mass (HM) and nutritive value of different canopy layers of stockpiled limpograss under continuous stocking from January to March in 2014 and 2015. Treatments were two limpograss cultivars (Floralta or Gibtuck) and three canopy layers (below 25 cm [CL0], 25-50 cm [CL25], or above 50 cm [CL50]) sampled biweekly. Gibtuck had greater HM (6.1 vs. 5.5 Mg ha(-1)) and in vitro digestible organic matter (IVDOM, 490 vs. 440 g kg(-1)) than Floralta. Herbage mass was 4.2, 3.3, and 1.0 Mg ha(-1) in January, 2.5, 3.2, and 0 Mg ha(-1) in February, and 3.4, 0.3, and 0 Mg ha(-1) in March for CL0, CL25, and CL50, respectively. The IVDOM concentrations were 380, 470, and 570 g kg(-1) in January for CL0, CL25, and CL50, and 390 and 450 g kg(-1) in February and 390 and 400 g kg(-1) in March for CL0 and CL25, respectively. Leaf proportion in the canopy decreased from CL50 to CL0. To meet the nutritional requirements of beef cattle grazing stockpiled limpograss pastures, it is necessary to adjust the supplementation quantity and composition during the stockpiling period due to the variation in HM, plant-part proportion, and nutritive value of the canopy.